Indices of Kidney Damage and Cardiovascular Disease Risk Factors in a Semiurban Community of Iloye, South-West Nigeria - J. O. Awobusuyi; O. O. Kukoyi; M. A. Ibrahim; M. Atiba (International Journal of Nephrology)
Health screening exercises are important, as they enable early detection of diseases in individual subjects and also enable data collection, useful in estimating disease burden in the community. This paper describes the findings of a health screening exercise conducted in a semiurban population of Iloye, by the Rotary Club of Ota, Ogun State, Western Nigeria, as a part of its community-oriented services and projects. Three hundred and twenty six community members were screened during the exercise. There were 189 (57.97%) females and 137 (42.03%) males, with a mean age of 43.5 ± 14.88 yrs. Urinary abnormality and/or creatinine clearance less than 90 mls/min was detected in 147 (45.09%) participants. 99 (30.37%) participants had proteinuria, 16 (4.91%) had haematuria, and 5 (1.53%) participants had both haematuria and proteinuria. Eight (2.45%) participants had GFR less than 60 mls/min. Elevated blood pressure was found in 152 (46.63%), while 3 (0.9%) participants had diabetes, 71 (21.8%) were obese, 16 (4.9%) had hypercholesterolaemia, and 3 (0.9%) had hypertriglyceridaemia. Prevalence of both smoking and alcohol consumption was 6 (1.84%). It was concluded that the prevalence of indices of kidney damage and cardiovascular risk factors is high in Iloye community.